PERAN POLISI RESORT SIMEULUE DALAM MENGAWASI PUTUSAN PENYELESAIAN PERSELISIHAN DI GAMPONG - Muammar Maulis Kadafi; Hamid Saroeng; Taqwaddin Taqwaddin (Jurnal Ilmu Hukum, 2016)
Abstract: Article 13 paragraph (1) Qanun No. 9/ Year 2008 regulates how to perform and to implement life and cultural custom. In the regulation of Qanun, the life of cultural and village structure (Gampong in Acehnese) is authorized to conduct dispute-settlements related to criminal problems firstly at the Gampong level. However, there has been a deviation in terms of its implementation as the community in East Simeulue performed this. They tend to clarify the dispute firstly at the police level. This study briefly explained the roles, obstacles, the peace treaty implementation in settling the dispute at Police Office at East Simeulue district at the Gampong level.Keywords: completion, decision, gampong disputes, police role, supervision. Abstrak: Pasal 13 ayat (1) Qanun Nomor 9/ Tahun 2008 mengatur tentang bagaimana penyelenggaraan dan pelaksanana kehidupan dan adat istiadat. Dalam ketentuan Qanun, kehidupan adat dan perangkat kampung (Gampong dalam bahasa Aceh) diberikan kewenangan untuk melakukan penyelesaian sengketa terkait kasus pidana terlebih dahulu pada tingkat gampong. Namun, ada sedikit ketimpangan dalam pelaksanaannya sebagaimana dilakukan oleh masyarakat Simeulue Timur. Mereka cenderung ingin menyeesaikan sengketa terlebih dahulu di tingkat kepolisian. Studi ini menjelaskan secara lugas peranan, hambatan, pelaksanaan putusan perdamaian dalam penyelesaian perselisihan di Polres Simeulue Timur ditingkat gampong.Kata kunci: penyelesaian, putusan, perselisihan kampong, peranan polisi, pengawasan.